2021
DOI: 10.1002/onco.13698
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Direct Oral Anticoagulants in Central Nervous System Malignancies

Abstract: Patients with brain tumors are at high risk for thromboembolic complications and frequently require anticoagulation. Direct oral anticoagulants (DOACs) are a less burdensome treatment for cancer‐associated thrombosis with safety and efficacy comparable to those of low molecular weight heparin (LMWH); however, there are few data to support the use of DOACs in patients with brain tumors. The purpose of this study was to better understand the safety profile of anticoagulants in patients with primary and metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
(39 reference statements)
1
21
0
1
Order By: Relevance
“…In our study, metastatic brain bleed only occurred in patients without verified cerebral metastases at inclusion. Several retrospective studies indicate a comparable safety profile between oral factor Xa inhibitors and LMWHs in patients with cerebral metastases and primary cerebral tumors 27–29 . The current data illustrates that the actual rate of patients with cerebral metastases is uncertain if you do not do cerebral CT‐scan at inclusion.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, metastatic brain bleed only occurred in patients without verified cerebral metastases at inclusion. Several retrospective studies indicate a comparable safety profile between oral factor Xa inhibitors and LMWHs in patients with cerebral metastases and primary cerebral tumors 27–29 . The current data illustrates that the actual rate of patients with cerebral metastases is uncertain if you do not do cerebral CT‐scan at inclusion.…”
Section: Discussionmentioning
confidence: 86%
“…When anticoagulation was analyzed as a time-varying covariate, the risk of any ICH did not differ between DOAC- and LMWH-treated patients (HR: 0.98; 95% CI 0.28 to 3.40) [ 46 ]. Finally, a single-center retrospective chart review of 125 patients with primary and metastatic brain tumors on anticoagulation reported rates of major bleeding of 26% and 9.6% in patients receiving LMWH or DOAC, respectively [ 47 ]. Patients receiving DOAC also had a lower rate of ICH compared to those receiving LMWH (5.8% vs. 15%) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a single-center retrospective chart review of 125 patients with primary and metastatic brain tumors on anticoagulation reported rates of major bleeding of 26% and 9.6% in patients receiving LMWH or DOAC, respectively [ 47 ]. Patients receiving DOAC also had a lower rate of ICH compared to those receiving LMWH (5.8% vs. 15%) [ 47 ]. Nevertheless, given the small numbers and the limitations of retrospective studies, as well the shorter half-life of LMWH, the consensus committee suggests considering the initial use of LMWH for patients with CAT and high-risk intracranial lesions (e.g., glioma).…”
Section: Discussionmentioning
confidence: 99%
“… 79 In the second chart review study (n=125), the rate of major bleeding was 9·6% under direct oral anticoagulants versus 26% under LMWHs (p=0·03), and the respective rates of intracerebral haemorrhage were 5·8% and 15% (p=0·09), with no difference in minor bleeding and recurrent VTE. 80 In the third study (n=111), the 6-month cumulative incidence of intracerebral haemorrhage was 4·3% (95% CI 0·74–13·2) with direct oral anticoagulants versus 5·9% (1·5–14·9) with LMWHs, and the 6-month cumulative incidence of bleeding was 14·3% (6·2–25·8) versus 27·8% (15·5–41·6), respectively. 81 Rates of recurrent VTE did not differ between groups.…”
Section: Vte Prophylaxis In Patients With Cancermentioning
confidence: 92%